2011
DOI: 10.1111/j.1600-0897.2010.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Plasminogen Activator Inhibitor‐1, Integrin Beta3, Beta Fibrinogen, and Methylenetetrahydrofolate Reductase Polymorphisms in Iranian Women with Recurrent Pregnancy Loss

Abstract: The data highlight the importance of thrombophilia screening in patients with RPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 46 publications
2
46
1
5
Order By: Relevance
“…Although several etiologies, such as anatomic defects of the uterus, immune disorders, endocrinological abnormalities and chromosomal translocations and inversions, have been recognized as causes of FL, the pathophysiology still remains unexplained (9,12,13). It has been suggested that acquired or inherited thrombophilia is associated with FL (9,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several etiologies, such as anatomic defects of the uterus, immune disorders, endocrinological abnormalities and chromosomal translocations and inversions, have been recognized as causes of FL, the pathophysiology still remains unexplained (9,12,13). It has been suggested that acquired or inherited thrombophilia is associated with FL (9,14).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of PAI-1 due to the presence of 4G/4G may contribute to the risk for deep vein thrombosis (DVT) and myocardial infarction (4,8). The PAI-1 overexpression and impaired fibrinolysis may also cause compromised and insufficient trophoblast invasion, leading to abnormal placental formation and increased risk of FL (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that PAI-1 4G/5G gene variant may be one of the risk factors for spontaneous miscarriage (10,11) and preeclampsia (12). Furthermore, increased expression of PAI-1 is associated with insulin resistance (13) and type 2 diabetes (14).…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, as frequências do alelo 455A nas mulheres com história de AER foi semelhante a encontrada em mulheres iranianas com até 35 anos de idade, com duas ou mais perdas gestacionais sucessivas até a vigésima semana de gestação (Jeddi-Tehrani et al, 2011), assim como a encontrada em indivíduos brasileiros (p>0,05) (Sampaio et al, 2007).…”
Section: Discussionunclassified
“…A associação entre os polimorfismos genéticos (FVL e protrombina) e os AER foi descrita, porém os resultados são controversos, uma vez que muitos não encontraram associação (Jivraj et al, 2006;Karata et al, 2011;Serrano et al, 2011;Dissanayake et al, 2012). Pouco se conhece sobre o papel de polimorfismos em outros genes relacionados a fatores ou inibidores da hemostasia, tais como de fatores e/ou inibidores associados a geração de trombina e fibrinólise e seu papel na etiologia de AER (Jeddi-Tehrani et al, 2011;Ticconi et al, 2011;Guerra-Shinohara et al, 2012;Su et al, 2013).…”
Section: Diminui a Concentração Anticoagulaçãounclassified